191 A classification of primary care pathways in emergency departments: a multi-methods study comprising cross-sectional survey; site visits with observations; semi-structured and informal interviews. Issue 12 (23rd November 2020) - Edwards, Michelle; Cooper, Alison; Freya, Davies; Carson-Stevens, Andrew; Hughes, Thomas; Siriwardena, Niro; Snooks, Helen; Edwards, Adrian
Abstract : Aims/Objectives/Background: We aim to describe and classify the predominant streaming pathways on arrival in Emergency Departments (EDs) in England and Wales and explain how they operate in different models of emergency department primary care services. Recent policy has encouraged a method whereby nurses stream from the emergency department front door to GPs working in a separate GP service operating within or alongside an ED. However, there is variation in methods of assessing and streaming patients on arrival at EDs. Conflated terminology causes difficulties in assessing relative performance, improving quality or gathering evidence about safety, clinical effectiveness. Our findings present a new classification of current streaming pathways from emergency departments to primary care services. Methods/Design: We used a multi-stage method approach, including an online survey completed by 77 EDs across England & Wales, interviews with 21 clinical leads, and finally, undertaking case studies of 13 EDs. Qualitative data were triangulated and analysed using a framework analysis approach. Results/Conclusions: The most common ED pathways to primary care services were: front door streaming before ED registration; streaming inside the ED; or without streaming but GPs selecting patients. Pathways were often adapted, to suit local circumstances such as department layout, patient demand levels, skill mix and interests of GPs practitioners and the accessibility of community primary care services. Pathways to redirect patients with non-urgent primary care problems to community primary care services were also used, with local variation in protocols based on staffing, patient demand and links to community primary care services. Local clinical leads and managers need to consider which pathway(s) may best suit their local context and needs. Consistency of terminology used to describe pathways between EDs and primary care services is necessary for multi-site evaluation, quality improvement and performance measurement.